Electrochemical preparation and characterization of poly(3-hexylthiophene)-cadmium sulfide hybrid semiconductor films - Ing, Yah Chzeh (2014)
Cadmium sulphide (CdS) is an interesting II-VI semiconductor with medium band gap (~2.4 eV) which can absorb visible light. In this study semiconducting CdS thin films were prepared using potentiostatic electrodeposition and pulse electrodeposition techniques on indium doped tin oxide (ITO)-coated glass substrate at room temperature. CdS thin films were deposited onto ITO coated glass from deposition bath containing 0.01 M CdSO4and 0.35 M Na2S2O3 and pH was adjusted to 3 using sulphuric acid. A three electrode-cell system was used where Ag/AgCl | 3 M NaCl as the reference electrode, platinum wire as the counter electrode and ITOcoated glass as the working electrode. Cyclic voltammetry was used to determine the suitable range of deposition potential and the potential range obtained was between – 0.75 V to –1.00 V. CdS thin films were deposited by applying various deposition potentials. XRD patterns showed that the as-deposited CdS thin films were polycrystalline with hexagonal structure with hkl planes corresponding to (100), (002), (101), (102), (103), and (110) reflections. The band gap energy of samples prepared by both techniques was found to be within the range of 2.40 – 2.42 eV with direct transition. Photoelectrochemical (PEC) properties of CdS films were measured, using linear sweep photovoltammetry by intermittently illuminating the samples immersed in 0.01 M Na2S2O3with a 300 W halogen lamp. Photocurrent was observed to be more apparent at anodic potential region. Thus, CdS is an n-type semiconductor. XRD and PEC results showed good quality film was obtained at deposition potential of –0.90 V. Cadmium sulfide thin films prepared by the pulse electrodeposition technique exhibit desirable optical properties as semiconductor material and better photoresponse compared with the films deposited by normal potentiostatic electrodeposition technique. Poly(3-hexylthiophene) thin films were deposited electrochemically onto ITO coated glass in a two-electrode cell, ITO coated glass was used as working electrode and platinum wire as the counter electrodefrom bath comprised of 0.05 M 3- hexylthiophene monomer and 0.10 M tetrabutylammonium tetrafluoroborate (TBATFB) in acetonitrile at deposition potential of 5 V. The effect of solution aging time on homogeneity of electrodeposited P3HT thin films was studied. A smooth adhered film was obtained using solution aged for 5 days. FTIR showed characteristic bands of 2, 5-disubstituted-3-alkylthiophene. Photocurrent were observed at the cathodic direction indicated that P3HT film deposited in this study is p-type semiconductor. The band gap energy of the prepared P3HT is 1.8 eV with indirect transition. Organic-inorganic hybrid films based on P3HT and CdS was fabricated by using electrochemical deposition method, a layer of CdS was pulse electrodeposited on P3HT film which was first deposited on ITO. Cyclic voltammetry of P3HT in bath containing supporting electrolytes showed that P3HT is stable in aqueous solution under applied potential and suitable to be used as base layer for cathodic electrodeposition of CdS. The optical properties were analyzed and the band gap energy was found to be 2.07 eV between that of P3HT films (1.8 eV) and CdS (2.4eV) with indirect transition. The photoelectrochemical properties were recorded in the form of current density-voltage curves showed CdS/P3HT presents a higher photocurrent response than that of pure P3HT and absorbs radiation in a wider region.